Empowering health and wellness for elderly in Wedoro Village - Syamsudduha Syahrorini; Andriani Eko Prihatiningrum; Denny Irawan; Yanik Purwanti; Agus Hayatal Falah; Shaza Dyah Ayuni; Akhmad Mulyadi; Andika Wahyu Nugraha; Fajrian Moch Bintang (Community Empowerment, 2024)
This community service involves the elderly and posyandu cadres in Wedoro Village, with the most common health issues being diabetes, high blood pressure, and temperature-related concerns. The objective of this service activity is to provide education and training to the residents of Wedoro Klurak Village, particularly the elderly posyandu members, to improve their health and enable them to conduct independent health checks. Methods for implementing this community service include outreach programs and urban farming training to cultivate organic plants as alternative medicine sources. The outcomes of this community service initiative include increased awareness of common metabolic diseases among the elderly. Urban farming training has brought joy to the elderly, promoting improved health through increased activity and productivity.